First and second order necessary optimality conditions for discrete optimal control problems - Marinković, B. (Yugoslav Journal of Operations Research; Vol 16 No 2 (2006): Vol. 16 No. 2, 2016)
Discrete optimal control problems with varying endpoints are considered. First and second order necessary optimality conditions are obtained without normality assumptions.